113 Characterising disease and prescribing patterns in patients with heart failure and multimorbidity: a single-centre descriptive cohort study. (6th June 2022) - Bahar, Jameela; Saied, Schabnam; Heron, Olivia; Mashida, Knievel; Akpan, Asan; Walker, Lauren; Alex, Elza; Sankaranarayanan, Rajiv
Abstract : Introduction: Heart failure (HF) co-exists with multi-morbidity like renal impairment, diabetes, chronic respiratory diseases, frailty and anaemia. The management of HF patients with multimorbidity is complex, involving numerous therapeutics, which have potential for drug-drug and drug-disease interactions. The aims of the study were:1. To characterise prescribing patterns in HF patients with multimorbidity2. To identify inappropriate polypharmacy and therefore targets for deprescribing. Methods: This was a retrospective cohort study involving patients under care of HF multimorbidity, multidisciplinary team at Aintree University Hospital from January 2020-February 2021. Data was extracted from 234 adult HF patients with multimorbidity. We also recorded age, sex, number of medications and presence/absence of inappropriate dual antiplatelet therapy (DAPT) and proton-pump inhibitor (PPI) use were recorded. Inappropriate medication use was determined according to NICE prescribing guidance. Age-adjusted Charlson Comorbidity Index (CCI), Rockwood Clinical Frailty score (CFS<6=mild/no frailty, ≥6+moderate/severe frailty) and anticholinergic burden (ACB) score were calculated. CFS of 7–9 was used to determine patients considered to be approaching end of life (12–24 months). Results: Mean age was 71.5±13.9 and 44% patients female. CCI was 6.9±3.3, Rockwood Frailty Score 5.5±3.2, polypharmacy burden high at 10.2±3.9 and ACB 1.45±0.9. ACB was higher in patients with CFS≥6 vs. those with CFS<6 (1.5±1.1 vs. 1.1±0.9;p=0.02). Proportion of HF patients on treatment for depression was 19.7%, chronic pain 35%, and chronic constipation 19.7%. Regular oral iron was prescribed in 15% of those appropriate for intravenous iron replacement. 17.9% of the cohort were estimated to be approaching end of life. Regarding potential inappropriate prescribing; 9% were on either DAPT/anticoagulant plus anti-platelet therapy beyond 12 months of acute coronary event. 20.1% patients were inappropriately prescribed regular PPI without clear indication. Conclusion: Frail HF patients have a higher ACB and this observational study identifies clear targets for de-prescribing intervention in HF patients, like inappropriate PPI and DAPT/anticoagulant plus anti-platelet therapy, affecting 1:5 and 1:10 patients in the clinic respectively. Clear de-prescribing guidelines for these medications should be developed to support shared decision making between patients and clinicians to reduce the drug burden in this complex cohort. Conflict of Interest: None